Biodiversity and globalization - Geoffrey Heal (Fondazione Eni Enrico Mattei (FEEM), 2002)
Reduction of the earth's biodiversity as a result of human activities is a matter of great concern to prominent scientists. What are the economic aspects of this loss? In economic terms, what is biodiversity and why might it matter? And is the loss of biodiversity in any way connected with globalization of the economy?
Keywords: 330; Biodiversity; public goods; globalization; bundling; Artenvielfalt; Globalisierung; Öffentliche Güter; Welt